Arabic And islamique educationin the contemporary world: prospect and challenge - Abdul-Hamid Habibullahi (Social Empowerment Journal, 2025)
The place of language in human activities is very significant as it servs as the major means of communication. It occupies a major position in the intellectual and spiritual development of Muslim communities in the world. This paper explores historical development of Arabic and Islamic Education in the world with special attention on it prospects and challenges. The paper conceptualizes Arabic and Islamic studies in the context of education. It follows the trends chronological development of Arabic and Islamic Education from the Asian continent to European; American, China and African continents. However, its relevance in contemporary educational discourse, especially in Western Nigeria, are undermined by numerous challenges. This paper examines the major impediments confronting Arabic and Islamic Education in Private Arabic Schools (PASs) across the region. Drawing upon recent literature and based on thematic content analysis, which entails the systematic review and synthesis of key emerging themes from existing literature, the study identifies critical issues such as the lack of standardized curriculum, insufficient of professionally trained teachers, inadequate infrastructure, limited local  Arabic and Islamic textbooks, and poor government support. It also highlights socio-political challenges including the stigmatisation of Arabic education due to weak foundations at the Ibtidaiyyah level, and restricted pathways to higher education for Arabic learners. The paper argues that these challenges stem from systemic neglect, curricular disconnection from national educational goals, and inadequate policy integration. The paper suggests curriculum reform, teacher professionalization, infrastructural improvement, and digital inclusion to enhance the quality and perception of Arabic and Islamic Education. A multi-sectoral collaboration between government, Islamic organizations, and private proprietors is also proposed to revitalize this vital component of Nigeria’s educational system.